Effect of Maternal Child‐Feeding Patterns on the Incidence of Stunting among Toddlers in Jombang Regency and Pasuruan City - Sugianti, Elya; Putri, Berliana Devianti; Hidayanti, Henny (Indonesian Journal of Human Nutrition, 2024)
Stunting remains a burden on national health development. One contributing factor to stunting is maternal child‐feeding patterns. Identifying maternal child‐feeding patterns is vital for selecting priority interventions. This study aims to analyze which maternal child‐feeding patterns most influence the incidence of stunting among toddlers aged 24-59 months in Jombang Regency and Pasuruan City. The study used a case-control design involving 292 respondents (146 cases and 146 controls) and collected data through interviews with structured questionnaires. Data were analyzed using univariate and multivariate logistic regression. The results showed that family size (p = 0.045), the starting time of early initiation of breastfeeding (p = 0.002), exclusive breastfeeding (p = 0.006), complementary feeding (p = 0.031), and formula feeding before 6 months (p = 0.003) affected the incidence of stunting among toddlers. Multivariate analysis revealed that the start time of early initiation of breastfeeding was the most influential factor in the incidence of stunting (p = 0.029; OR = 0.537; 95% CI: 0.307-0.939). Health workers should encourage mothers to initiate breastfeeding early and maintain it for an adequate duration.